Effect of deicers on germination of buried seeds in topsoil of old field - Shin, Seung Sook; Shin, Eun Ju; Park, Sang Deog; Lee, Kyu Song (KSCE journal of civil engineering, 2012)
This article presents that deicers such as calcium chloride (CaCl 2 ) and EFDs (Eco-Friendly Deicers) composed with organic acids affect germination of seeds buried in old-field soil. CaCl 2 , one of a commonly used deicer in the world, have shown an inhibitory effect on the germination of the buried seeds. Species richness, species diversity, and total biomass of the plant community after germinating were greatly decreased with increase of CaCl 2 concentration. The germination of buried seeds was inhibited seriously by CaCl 2 , but the degree of its varied significantly with plant species. EFD1 manufactured from organic chemicals showed the higher inhibition on germination than CaCl 2 . However, EFD2 composed with organic acids of food waste didn’t have an inhibitory effect on the species richness after germination and rather enhanced the germination and initial growth of the seedlings. The positive effect was evaluated that EFD2 caused to supply nutrition on germination or growth of buried seeds. The deicers may change dynamically the plant community of the roadside because the response of germination and growth by deicers differ from plant species.